2010
DOI: 10.1371/journal.pone.0010752
|View full text |Cite
|
Sign up to set email alerts
|

Motion Sickness, Stress and the Endocannabinoid System

Abstract: BackgroundA substantial number of individuals are at risk for the development of motion sickness induced nausea and vomiting (N&V) during road, air or sea travel. Motion sickness can be extremely stressful but the neurobiologic mechanisms leading to motion sickness are not clear. The endocannabinoid system (ECS) represents an important neuromodulator of stress and N&V. Inhibitory effects of the ECS on N&V are mediated by endocannabinoid-receptor activation.Methodology/Principal FindingsWe studied the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 37 publications
8
92
1
2
Order By: Relevance
“…It is interesting to note, that migraineurs are more susceptible to motion sickness than controls probably due to the ineffective top‐down control on relevant brainstem areas in response to excessive or stressful sensory inputs (Cuomo‐Granston & Drummond 2010). Regarding motion sickness, it has been demonstrated that those who respond with acute motion sickness to parabola flight have significantly higher stress scores accompanied by increased salivary cortisol concentration, lower whole blood endocannabinoid levels and decreased CB1 mRNA leukocyte expression compared to those with no motion sickness (Chouker et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note, that migraineurs are more susceptible to motion sickness than controls probably due to the ineffective top‐down control on relevant brainstem areas in response to excessive or stressful sensory inputs (Cuomo‐Granston & Drummond 2010). Regarding motion sickness, it has been demonstrated that those who respond with acute motion sickness to parabola flight have significantly higher stress scores accompanied by increased salivary cortisol concentration, lower whole blood endocannabinoid levels and decreased CB1 mRNA leukocyte expression compared to those with no motion sickness (Chouker et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Those severe, fast-changing conditions heavily impact on the human sense of balance, leaving the subjects with only little control of their well-being and no possibility to escape the situation and therefore causing acute stress (Schneider et al, 2007(Schneider et al, , 2009Chouker et al, 2010).…”
Section: Acute Vs Chronic Stressmentioning
confidence: 99%
“…On the ISS, blood vials were stored at -80 ° C until downloaded to Earth and analyzed ( Figure 5 ). The details of the high-performance liquid chromatography tandem mass spectrometry technique used for EC quantification are described elsewhere (Vogeser et al, 2006;Chouker et al, 2010).…”
Section: Ec and Glucocorticoid Measurements And Stress Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…27 A recent study has suggested a negative relationship between the concentrations of plasma endocannabinoids and the activity of the HPA axis in stressed humans. 36 Several studies in animals have shown that increased glucocorticoid concentrations in several stress-activated brain areas were associated with reduced AEA concentrations in these regions. 37,38 In this work, a validated analytical method to detect cortisol, cortisone, AEA, and 2AG in hair samples is presented.…”
Section: Introductionmentioning
confidence: 99%